Use of Mobile Devices to Access Resources Among Health Professions Students: A Systematic Review. Issue 1 (2nd January 2016) - Mi, Misa; Wu, Wendy; Qiu, Maylene; Zhang, Yingting; Wu, Lin; Li, Jie
ABSTRACT: This systematic review examines types of mobile devices used by health professions students, kinds of resources and tools accessed via mobile devices, and reasons for using the devices to access the resources and tools. The review included 20 studies selected from articles published in English between January 2010 and April 2015, retrieved from PubMed and other sources. Data extracted included participants, study designs, mobile devices used, mobile resources/apps accessed, outcome measures, and advantages of and barriers to using mobile devices. The review indicates significant variability across the studies in terms of research methods, types of mobile programs implemented, resources accessed, and outcomes. There were beneficial effects of using mobile devices to access resources as well as conspicuous challenges or barriers in using mobile devices.